Experimental Study on the Behavior of X-Section Pile Subjected to Cyclic Axial Load in Sand - Yiwei Lu; Hanlong Liu; Changjie Zheng; Xuanming Ding (Shock and Vibration)
X-section cast-in-place concrete pile is a new type of foundation reinforcement technique featured by the X-shaped cross-section. Compared with a traditional circular pile, an X-section pile with the same cross-sectional area has larger side resistance due to its larger cross-sectional perimeter. The behavior of static loaded X-section pile has been extensively reported, while little attention has been paid to the dynamic characteristics of X-section pile. This paper introduced a large-scale model test for an X-section pile and a circular pile with the same cross-sectional area subjected to cyclic axial load in sand. The experimental results demonstrated that cyclic axial load contributed to the degradation of shaft friction and pile head stiffness. The dynamic responses of X-section pile were determined by loading frequency and loading amplitude. Furthermore, comparative analysis between the X-section pile and the circular pile revealed that the X-section pile can improve the shaft friction and reduce the cumulative settlement under cyclic loading. Static load test was carried out prior to the vibration tests to investigate the ultimate bearing capacity of test piles. This study was expected to provide a reasonable reference for further studies on the dynamic responses of X-section piles in practical engineering.